Peran Pendampingan Warga Peduli AIDS terhadap Kualitas Hidup Orang Dengan HIV-AIDS di Kecamatan Alak Kota Kupang - Chintya G. Kale; Tadeus A. L. Regaletha; Amelya B. Sir (Lontar : Journal of Community Health, 2019)
HIV-AIDS still be the global healthy problem which has higer number of morbidity and mortability cases. PLWA (People Live With AIDS) have often being denied by the others so the HIV-AIDS problem sometimes is undetected in the society, also give the influence towards the quality of PLWA’s life. The quality of life is the important component of life and welfare evaluation of the PLWA. Based on the data of Alak districst in 2018, the higest case was 185 cases of HIV-AIDS in which the HIV infectants were 102 cases, while people with AIDS were 83 cases. This research is purposed to describe the quality of life of People Live With HIV-AIDS in Alak district in 2019 whose got accompaniment from the WPA ( PCWA : People Who Care With AIDS) companions. This research was done by using descriptive qualitative method. The main informants of this research were two WPA (PCWA) companions and five PLWA whose got the accompaniment also supported by three triangulation informants. The technique of data collection of this research was indeep interview whith three steps of interactive analitical models which are Reduction, Data Presentation and conclusion drawing. The result of this research shows that the implementation of the role of the PCWA as the mentors of taking medication, social supporter, and health service access support was successful and gave the impact towards PLWA’s Life. It’s shown by looking to the improvement of physical aspect, psychological aspect, independency, social relationship, sociaty aspect and spiritual aspect. This accompaniment had occured for almost 4 years towards the PLWA. It was expected for the other people to participate helping the PCWA companions in order to support and conducive towards the PLWA so, they have better quality of life.